To Compare the Efficacy of Bolus Dose of Propofol versus Control in Patients Undergoing Elective Cesarean Section under Spinal Anesthesia (Medical Forum Monthly, 2022)
Objective: The compare the efficacy of bolus dose of Propofol versus control in patients undergoing elective cesarean section under spinal anesthesia.Study Design: Randomized controlled trial studyPlace and Duration of Study: This study was conducted at the Department of Anesthesia, Dow University of Health Sciences and Civil Hospital, Karachi from 1st January 2018 to 30th June 2018.Materials and Methods: All women aged 18-38 years presented with full-term, para 0-5, weight between 50–75 kg, ASA class I & II underwent elective cesarean section under spinal anesthesia were included. Participants were randomly allocated equally to the control group (Group C) or Propofol groups (Group P) using a lottery method. Efficacy was labeled as positive if there was no vomiting intraoperatively.Results: Mean age of the women was 32.89 ±4.03 years. The mean weight, height, and BMI of the women were 60.07±5.12kg, 1.54±0.06m, and 26.98±5.15kg/m2 respectively. Efficacy was found 42 (93.3%) significantly higher among women with propofol as compared to placebo 30 (66.7%) (p=0.002).Conclusion: The efficacy of bolus dose of propofol was found higher among control in patients undergoing elective cesarean section under spinal anesthesia.